Pengaruh Asset Growth, Sales Growth, Net Profit Margin, Current Ratio dan Debt To Equity Ratio terhadap Dividend Payout Ratio pada Perusahaan yang Termasuk dalam Indeks Lq 45 Tahun 2013 – 2016 - Mufidah Mufidah (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research aimed to examine  theinfluence of Asset Growth, Sales Growth, Net Profit Margin , Current Ratio , debt to equity ratio on dividend payout ratio of the Company listed in indeks LQ 45 . The data used in this research is 16 companies for the period of 2013 – 2016 . The method of data analysis uses multiple linear regression. The result indicates that simultaneously the variable of Asset Growth, Sales Growth , Net Profit Margin, Current Ratio, debt to equity ratio significant affect divident payout ratio. These independent variables are able to explain the effect dividend payout ratio amount of 83,7 % while the remains 16,3 % is determined by other factors. Partially all of the variables  affect dividend payout ratio except of the variable of net profit margin. Sales growth had positive effect on dividend payout ratio . Beside that aset growth, current ratio and debt to equity ratio have  a negative effect on dividend payout ratio. Keywords: dividend payout ratio ,Sales Growth